A triple bottom line examination of product cannibalisation and remanufacturing: a review and research agenda - Okorie, Okechukwu; Obi, Martins; Russell, Jennifer; Charnley, Fiona; Salonitis, Konstantinos (Elsevier, 2021)
Increased momentum in support of a Circular Economy (CE) has motivated the exploration of alternative production and value-retention processes that allow for the decoupling of environmental impacts from economic growth. Remanufacturing, a key value retention process, can enable significant economic, environmental and social (also known as triple-bottom line) advantages. Given their competitive value proposition, remanufactured products are often blamed by original equipment manufacturers (OEMs) for cannibalising the sale of newly manufactured products. Thus, remanufacturing is often viewed as high-risk, and potentially even a threat to conventional manufacturing activities by many OEMs, often triggering both active and passive countermeasures to protect market share. In many cases, such actions lead to reduced access to cores for remanufactures; they can also work against the uptake of remanufacturing activities that are essential for transitioning to a CE. To achieve a CE, remanufacturing activities must be scaled; however, without a clear understanding of the relationship between remanufacturing and product cannibalisation, OEMs may continue to avoid and/or interfere in remanufacturing systems. Further, in alignment with systems-thinking for CE, we posit that broadly-considered integration of CE dimensions is critical but lacking within the literature. To this end, this systematic review paper aims to clarify and organize the existing scientific literature about product cannibalisation and remanufacturing. We examine these contributions through an expanded Triple Bottom Line lens that aligns with the recognized dimensions of CE: social, environmental, economic, management, policy, and technology. A comprehensive content assessment revealed a predominant economic lens to the research, with statistical analysis, game theory, and numerical experiments as the primary methodologies employed. In addition, opportunities to more comprehensively explore social, policy, management, and technology perspectives as they relate to product cannibalisation and remanufacturing were identified. We develop and apply a new framework for considering product cannibalisation and price competition in the broader context of sustainability and the transition to CE. Finally, in addition to identifying a comprehensive range of stakeholders that need to be engaged, we recommend a future research agenda that explores the specific challenges, interactions, and relationships between product cannibalisation, remanufacturing, and the six dimensions of CE.
Keywords: triple bottom line; systematic review; cannibalisation; circular economy; Remanufacturing